Use of del Nido cardioplegia in adult cardiac surgery - Amaç, Bişar; Selçuk, Mümün; Bölükbaş, Semra; Kahraman, Fatma; As, Ahmet Kağan; Savran, Muhammed; Güvenç, Orhan; Göncü, Mehmet Tuğrul; Engin, Mesut; Yavuz, Senol (The European Research Journal, 2022)
In most adult cardiac surgery operations, the heart must be completely immobile and isolated from the blood. Therefore, the heart is stopped in diastole and a still operative site is obtained. Cardiac arrest results in ischemia-reperfusion injury. For these reasons, myocardial protection and the prevention of damages are required. Various cardioplegia solutions are used for this purpose. It can be said that cardioplegia is the gold standard method of myocardial protection in cardiac arrest. Nowadays, "Single-dose cardioplegia" applications are increasingly used, especially in minimally invasive cardiac surgery and basic coronary bypass procedures due to the advantages they provide, which include reduction of aortic cross-clamp time, prevention of frequent interruption of the procedure due to cardioplegia, and reduced postoperative myocardial dysfunction incidence. The two main solutions used in single dose cardioplegia applications are the Bretschneider solution and the del Nido extracellular cardioplegia solution. The del Nido cardioplegia solution (dNCS), which was originally developed for use in pediatric cardiac surgery, has recently increased its use in adult cardiac surgery due to straightforward application and long-term effectiveness. The del Nido cardioplegia reduces the aortic cross clamp duration, cardiopulmonary bypass time and required cardioplegia solution volume, and is a safer and superior cardioplegia solution and technique in terms of myocardial protection with regards to many organs and cardiac-biochemical parameters.